2018
DOI: 10.1016/j.biocon.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes and drivers of freshwater mussel diversity and distribution in northern Borneo

Abstract: Human activities are threatening Borneo's unique biodiversity, but little is known on the status of freshwater invertebrates. We assessed changes in diversity and distribution of freshwater mussels (Bivalvia: Unionida) in northern Borneo, and identified drivers of present distribution and threats. Past distribution data were collected from literature and museum resources. Present distribution data were collected from 21 river basins, and 47 water quality, climatic, landscape and human variables explored as pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…Subsequently, the main pressing challenge in our effort to effectively conserve and manage freshwater biodiversity in Sabah is in identifying the minimum units of conservation (Woodruff, 1989) among these fragmented habitats. We reiterate the call by Zieritz et al (2018) to identify freshwater "biodiversity hotspots" (sensu Myers, Mittermeier, Mittermeier, da Fonseca, & Kent, 2000) in Borneo, which the authors noted would entail more thorough studies of species-level diversity. Intra-population diversity has been similarly side-lined in defining biodiversity hotspots even though incorporating molecular data could augment this approach by helping us delimit and delineate evolutionarily significant units (ESUs) within taxa, with particular interest on those with low genetic diversity and potentially low adaptive capacity.…”
Section: Implications For Conservation Of Local Freshwater Biodivermentioning
confidence: 81%
“…Subsequently, the main pressing challenge in our effort to effectively conserve and manage freshwater biodiversity in Sabah is in identifying the minimum units of conservation (Woodruff, 1989) among these fragmented habitats. We reiterate the call by Zieritz et al (2018) to identify freshwater "biodiversity hotspots" (sensu Myers, Mittermeier, Mittermeier, da Fonseca, & Kent, 2000) in Borneo, which the authors noted would entail more thorough studies of species-level diversity. Intra-population diversity has been similarly side-lined in defining biodiversity hotspots even though incorporating molecular data could augment this approach by helping us delimit and delineate evolutionarily significant units (ESUs) within taxa, with particular interest on those with low genetic diversity and potentially low adaptive capacity.…”
Section: Implications For Conservation Of Local Freshwater Biodivermentioning
confidence: 81%
“…The Isthmus of Kra as a significant biogeographic barrier for the Unionidae. It was shown that freshwater basins of the Malacca Peninsula represent a part of the Sundaland Subregion 16,17 and that the Dawei and Tanintharyi river basins belong to the Western Indochina Subregion 4,5,7,24 . However, the location of the southern boundary of the Western Indochina Subregion was until now unclear, because freshwater mussel faunas of the southern edge of Myanmar south of the Tanintharyi Basin were almost unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Muar River is a mesotrophic river (* 7-11 m wide) that flows through a mosaic of oil palm plantation and secondary forest, several km from the nearest human settlement ( Table 1). The only mussel present in the lake is the non-native Sinanodonta woodiana Lea, 1834, which is native to China and Russia, and has been widely introduced in ponds and rivers across Malaysia (Watters, 1997;Zieritz et al, 2016Zieritz et al, , 2018b. The river features two native mussel species, Contradens contradens (Lea, 1838) and Monodontina vondembuschiana (Lea, 1840) .…”
Section: Study Sitesmentioning
confidence: 99%